2012
DOI: 10.1242/jeb.065144
|View full text |Cite
|
Sign up to set email alerts
|

Small organ size contributes to the slow pace of life in tropical birds

Abstract: Recently, we demonstrated that tropical birds have an 18% lower BMR, 34% lower PMR C and 39% lower PMR E compared with temperate species (Wiersma et al., 2007a;Wiersma et al., 2007b). Along with a reduced metabolism, tropical birds tend to have a smaller clutch size than their temperate counterparts (Cardillo, 2002;Kulesza, 1990) Accepted 25 January 2012 SUMMARY Attributes of an animalʼs life history, such as reproductive rate or longevity, typically fall along a ʻslow-fastʼ continuum. Animals at the fast end … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 87 publications
3
40
2
Order By: Relevance
“…In one of these studies, the selection for increased metabolic rate led to an increase in relative internal organ size (Brzek et al, 2007). Given that metabolic rate and relative internal organ size are positively correlated (Holliday et al, 1967;Wiersma et al, 2012), it seems likely in this case that selection for increased metabolic rate led to an increase in organ size, rather than changes in fatty acyl composition. Hamsters fed diets high in different PUFA did not have differences in resting metabolic rate, though differences in tissue unsaturation index were not confirmed and dietary manipulations of PUFA concentration are notorious for not changing unsaturation index without extreme and often unhealthy dietary changes Pannorfi et al, 2012).…”
Section: Membrane Pacemaker Hypothesis Of Metabolismmentioning
confidence: 97%
“…In one of these studies, the selection for increased metabolic rate led to an increase in relative internal organ size (Brzek et al, 2007). Given that metabolic rate and relative internal organ size are positively correlated (Holliday et al, 1967;Wiersma et al, 2012), it seems likely in this case that selection for increased metabolic rate led to an increase in organ size, rather than changes in fatty acyl composition. Hamsters fed diets high in different PUFA did not have differences in resting metabolic rate, though differences in tissue unsaturation index were not confirmed and dietary manipulations of PUFA concentration are notorious for not changing unsaturation index without extreme and often unhealthy dietary changes Pannorfi et al, 2012).…”
Section: Membrane Pacemaker Hypothesis Of Metabolismmentioning
confidence: 97%
“…Evidence of a linkage between slow pace of life and low rate of metabolism in tropical birds came to light when it was shown that they had a significantly lower wholeanimal basal metabolic rate (Wiersma et al, 2007a) and peak metabolic rate as measured by cold-exposure or by exercise (Wiersma et al, 2007b). Later it was discovered that a contributing factor to the reduced rate of metabolism in tropical birds was their smaller metabolically active organs, such as the heart, liver, kidneys and pectoral muscles, compared with similar-sized temperate species (Wiersma et al, 2012). These findings offer evidence of a connection between the life history of tropical birds and their physiology, at least at the organismal and organ levels.…”
Section: Introductionmentioning
confidence: 99%
“…We think that part of the increase in self-maintenance of tropical birds manifests itself in a slower pace of life, reflected in decreased BMR and PMR, smaller metabolically active organs, and lower cellular metabolic rate [28], [29], [87]: collectively all of these are aspects of the birds’ physiology which positively correlate with increased survival. Physiological and fitness costs of particular life-history choices are dependent on environmental conditions [10], and it is difficult to separate the influences of climate per se and life-history attributes.…”
Section: Discussionmentioning
confidence: 98%
“…Our results suggest that isolated fibroblasts and myoblasts had the same metabolic profile, which suggests that fibroblasts are a representative cell system for the organism. Additionally, cellular metabolic differences could also occur for other organs, and since tropical birds generally have smaller metabolically active organs [87], then both cellular metabolic rates and organ masses are likely to alter organismal metabolic rate differences.…”
Section: Discussionmentioning
confidence: 99%